Altered levels of dopamine transporter in the frontal pole and dorsal striatum in schizophrenia - Sekiguchi, Hirotaka (NPJ Schizophr, 2019)
The dopamine hypothesis proposes that there is a hypodopaminergic state in the prefrontal cortex and a hyperdopaminergic state in the striatum of patients with schizophrenia. Evidence suggests the hyperdopaminergic state in the striatum is due to synaptic dopamine elevation, particularly in the dorsal striatum. However, the molecular mechanisms causing disrupted dopaminergic function in schizophrenia remains unclear. We postulated that the dopamine transporter (DAT), which regulates intra-synaptic dopamine concentrations by transporting dopamine from the synaptic cleft into the pre-synaptic neuron, could be involved in dopaminergic dysfunction in schizophrenia. Therefore, we measured levels of DAT in the cortex and striatum from patients with schizophrenia and controls using postmortem human brain tissue. Levels of desmethylimipramine-insensitive mazindol-sensitive [(3)H]mazindol binding to DAT were measured using in situ radioligand binding and autoradiography in gray matter from Brodmann’s area (BA) 10, BA 17, the dorsal striatum, and nucleus accumbens from 15 patients with schizophrenia and 15 controls. Levels of desmethylimipramine-insensitive mazindol-sensitive [(3)H]mazindol binding were significantly higher in BA 10 from patients with schizophrenia (p = 0.004) and significantly lower in the dorsal striatum (dorsal putamen p = 0.005; dorsal caudate p = 0.007) from those with the disorder. There were no differences in levels of desmethylimipramine-insensitive [(3)H]mazindol binding in BA 17 or nucleus accumbens. These data raise the possibility that high levels of DAT in BA 10 could be contributing to lower synaptic cortical dopamine, whereas lower levels of DAT could be contributing to a hyperdopaminergic state in the dorsal striatum.